Mass Spectrometry Analysis of Chromium-Binding Low-Molecular-Weight Serum Fractions - Anna Safitri; Aviva Levina; Peter A Lay (The Journal of Pure and Applied Chemistry Research, 2017)
The current work is focused on the characterization of the chromium(III)-containing low-molecular-weight (LMW) fractions of blood serum by mass spectrometry. The LMW fractions of serum binding-Cr(III) were collected by organic solvent precipitation using acetonitrile. The chromium(III) compounds used were [Cr(pic)3], where pic = 2-pyridinecarboxylato(-) or A, and the Cr(III) propionate complex, [Cr3O(OCOEt)6(OH2)3])+ or B. The new signals appeared in the mass spectra in the presence of added Cr(III) compounds, either A or B. This indicated that common LMW Cr containing serum fractions were formed on addition of Cr(III) to serum. The new signals contained three distinct peaks with a shift of 16, corresponding to ions of m/z +1083, +1099, and +1115 Da, which consisted of 4 Cr atoms with bridging ligands.